Pengembangan Model Permainan PARSI Terhadap Keterampilan Motorik Siswa Sekolah Dasar - Lihawa, Pardan S; Said, Hariadi; Ikhsan, Haerul (Universitas Negeri Gorontalo, 2025)
The research problem addressed in this study is: is the PARSI game feasible as a tool to assess motor skills in elementary school students? Thus, this study aims to determine the feasibility of developing the PARSI game as a means of assessing the motor skills of lower-grade elementary school students school students by utilizing the research and development (RD) method. Field trials and data analysis indicate that this study has successfully developed the PARSI game for enhancing elementary school students’ motor skills. The findings show that game experts rated 15 aspects with a score of 12 out of 15 (80%), learning experts provided the same score of 12 out of 15 (80%), and student questionnaire responses averaged 89%.